A Systematic Review of Studies on L2 Collocational Knowledge among Non-native English Learners - Wu, Yong Ping; Halim, Hasliza Abd; Nordin, Nur Rasyidah Mohd (CENTRAL ASIA AND THE CAUCASUS, 2021)
More and more studies came up to investigate L2 collocational knowledge among non-native English learners and yielded fruitful findings. However, there is a dearth of re- views on these studies, and not a systematic review is found. The present study employed “two-stage reviews” strategy for a systematic review. The first stage of review presents a description of the distribution of 115 existing articles, showing that studies are mainly concentrated in Asian countries. Participants are mainly EFL learners and distributed in university setting. Though productive knowledge are more examined than receptive knowledge, studies employing written learner corpora or writing tasks with large scale of data are in deficiency. At the second-stage, the present paper carried out an in-depth review of 36 articles and discussed learners’ problems in L2 collocation production, showing that learners have difficulties in both of accurate use and diverse use of L2 collocations. The problems in lexical collocations are significant and mainly related to lexical choice. Verb-noun collocations cause great problems to L2 learners. L2 learners generally lack the concept of English collocations and often fail to notice collocation restrictions. Additionally, the present study provides some directions for future research and teaching practice.